2016
DOI: 10.1101/054734
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substoichiometric molecular control and amplification of the initiation and nature of amyloid fibril formation: lessons from and for blood clotting

Abstract: The chief and largely terminal element of normal blood clotting is considered to involve the polymerisation of the mainly α-helical fibrinogen to fibrin, with a binding mechanism involving ‘knobs and holes’ but with otherwise littl change in protein secondary structure. We recognise, however, that extremely unusual mutations, or mechanical stressing, can cause fibrinogen to adopt a conformation containing extensive β-sheets. Similarly, prions can change morphology from a largely alpha-helical to a largely β-sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

7
0

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 472 publications
0
5
0
Order By: Relevance
“…However, this is not true for amyloid fibre formation [ 56 ] nor in the case of the autocatalytic conversion of prion protein conformations [ 57 , 58 ]. At present, the exact mechanisms of action of these small amounts of LPS are not known, although it is indeed simplest to recognize fibrinogen polymerization as a cascade effect, much as occurs for amyloid and prion proteins whose initial conformation is not in fact that of their lowest free energy [ 59 ]. Specifically [ 60 ], the ‘normal’ conformational macrostate of such proteins is not in fact that of the lowest free energy, and its transition to the energetically more favourable ‘rogue’ state is thermodynamically favourable but under kinetic control, normally (in terms of transition state theory) with a very high energy barrier Δ G † of maybe 36–38 kcal mol −1 [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not true for amyloid fibre formation [ 56 ] nor in the case of the autocatalytic conversion of prion protein conformations [ 57 , 58 ]. At present, the exact mechanisms of action of these small amounts of LPS are not known, although it is indeed simplest to recognize fibrinogen polymerization as a cascade effect, much as occurs for amyloid and prion proteins whose initial conformation is not in fact that of their lowest free energy [ 59 ]. Specifically [ 60 ], the ‘normal’ conformational macrostate of such proteins is not in fact that of the lowest free energy, and its transition to the energetically more favourable ‘rogue’ state is thermodynamically favourable but under kinetic control, normally (in terms of transition state theory) with a very high energy barrier Δ G † of maybe 36–38 kcal mol −1 [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that LPS can potently induce amyloid formation in fibrin (258, 259, 1084, 1085). Thus, in addition, we note the increasing recognition that amyloid proteins themselves, that may occur as a result of coagulopathies, are themselves both inflammatory [e.g., Ref.…”
Section: Clotting Coagulopathies and Fibrinogen In Pementioning
confidence: 99%
“…In a recent development, 232 , 255 , 256 we have shown that the fibrin dense-matted deposits of the type shown in Figure 4(b) can be generated by tiny amounts of LPS, and that they are actually β-amyloid in nature. This has significant implication more generally, 257 including diseases such as sepsis 258 and pre-eclampsia. 259 Amyloid fibrils of various kinds are widely recognized as inflammatory and cytotoxic (e.g.…”
Section: A Note On Amyloidogenesis and Amyloidoses In Ramentioning
confidence: 99%